Electric Vehicle Charge Station - Sowaity, Abed Alfattah; abu Hadwan, Sameer; Tomaizei, Raed (جامعة بوليتكنك فلسطين - طاقة, 2020)
أصبحَ التوجه الى استخدام التنقل الكهربائي أكثر من أيِ وقتٍ مضى في قطاع النقل بسبب تضرر البيئة لارتفاع نسبة ثاني اكسيد الكربون في الجو نتيجة استعمال السيارات التي تعمل بواسطة محركات الاحتراق الداخليومن أهم هذه الطرق الصديقة للبيئة للتنقل هي السيارات الكهربائية . والسيارات الكهربائية تعملُ في المقام الأول بواسطة محرك كهربائي يتم تغذيتة بواسطة مصدر طاقة قابل لأِعادة الشحن وهي البطاريات حيث يعادُ شحنُها باستخدام شاحن كهربائي خاص . في هذا المشروع سيتم دراسة السيارات الكهربائية ومكوناتها ووظيفة كل مُكون وكذلك التقنات المستخدمة فيها و البطاريات بأنواعها ونظام إدارة البطارية وتقنية شحن السيارات الكهربائية ومستويات الشحن وانماط الشحن وأنظمة الشحن حسب المعايير والمقاييس العالمية المعتَمدة.وأيضا سَيتم عرض أهم التِقَنيات الحديثة حول أجهزة شحن السيارات الكهربائية,وبالتالي من خلال هذه الدراسة بالإِمكان أخذ الصورة العامة وفهم أنظمة شحن السيارات الكهربائية . الهدف النهائي للمشروع هو تصميم نموذجلِمحطة شحن للمَركبات الكهربائية حسب المواصفات والمعايّر العالمية المعتمدة بأستخدام برنامج (MATLAB).   Electric Vehicle Charge Station The trend towards using electric mobility has become more than ever in the transportation sector due to the environmental damage and the high level of carbon dioxide in the atmosphere as a result of the use of cars that are powered by internal combustion engines. Electric cars are primarily powered by an electric motor that is fed by a rechargeable power source which is the batteries where they are recharged using a special electric charger. In this project, the electric vehicle and their components, the function of each component will be studied, as will the technologies used and the batteries of all kinds, Batteries, Battery Management System, the charging technologies of electric vehicles, related standards, charging levels, charging modes and Charging Schemes are described. Also, EV charging sockets are explained clearly. The whole issue about chargers is presented for commercial EV manufacturers. Consequently, the big picture of the electric vehicle charging system could be easily seen in this project. The main aim of this project is the design and implementation of an electric vehicle charge station with the international protocols and standards for electric vehicles using MATLAB
CD , no of pages 89 , طاقة 2/2020
Keywords: Electric Vehicle Charge